FENOMENA REMAJA MUALAF DI KOTA PEKANBARU - Yani, Alfiah Isti; Wirman, Welly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Converts and maintain the status of converts is not an easy thing for a teen, teen convert had to pass through a critical period like the inner struggle in deciding converting, then run consequences given people around him who did not approve of his decision, bleak in the isolate, in derision, and in exile. Teens in the know bring his personality into thinking and often experience instability or lack konsintenan, teens are also easily influenced by the surrounding environment. This study aims to reveal the communication experience of Youth converts in Pekanbaru.This study uses qualitative research with phenomenological approach. Subjects were aged 3 informant converts adolescence in Pekanbaru, obtained using purposive technique. The collection of data obtained through interviews, observation (observation) and literature.These results indicate that the motive teenage converts in Pekanbaru City consists of a motive because (Because motive) that is divine direction / guidance, the search for identity, the perception of good, feel differently. While the motive for (in order to motive) into a better human being, a sense of comfort, closer to God, faith desire. Meanings given by teenage convert to convert its status is converting is nothing in regret, converting a guidance, becoming more recognized and accepted the crowds, and became calmer. The communication experience is categorized into two, namely a pleasant communication experience such a warm welcome, supported and assisted, accepted and recognized. Communication experience unpleasant as debates, in isolate, are not recognized and in exile.Keywords: teen convert, motive, meaning, communication experience